JURIDICAL REVIEW OF A LIMITED COMPANY IF ACTING AS A LIMITED LIABILITY COMPANY IN A COMMANDITARE VENNOOTSCHAP COMPANY - Sudarno Sudarno (Justicia Journal, 2023)
As a legal entity (rechpersoon), a PT also holds the status of a legal subject. Included in the definition of legal subject is human (naturlijke persoon) and legal entites (rechpersoon) such as PT, state companies, foundations, government agencies and so on.As a legal subject, PT has rights and obligations and can enter into legal relations (rechtsbetrekking/rechtsverhouding). In addition, based on the fictie theory it is also stated that legal entities are considered the same as humans (persoon) as a legal subject. Therefore legal entities are also given the same rights and obligations as humans (persoon) in general.Commanditare Vennootschap a form of business entity formed by two or more people who then entrust their capital to two or more people. This was done to run the company as well as entrusted to lead the company. The goal is to achieve common goals with the level of involvement of each member, so some experts argue that CV consists of limited partners and complementary partners. Limited partners (passive partners) have the responsibility to provide CV capital to complementary partners (active partners) who are responsible for carrying out CV activities. Based on this background, in this thesis two problems aries, namely: 1. Is it possible and justifiable for a PT to become and active shareholder in the CV arrangement and what is the legal basis. 2. What if a PT becomes a passive participant in the CV, then with what concept so that this collaboration can run legally. To answer these problems, the Statute approach is used so that information will be obtained from various aspects regarding legal issues that are being tried to find answers. This Law approach is carried out by examining all laws and regulations that are related to legal issues related to the issues that are discussed in writing this thesis.After discussing the existing problems, it can be concluded that if this is based on this, then in general it is legally possible for every legal subject to carry out a legal action so that a limited liability company (PT) which is the subject of a Recht Persoon for cooperation in a Business Entity in the form of Limited Partnership (CV) both as active (Complementary) and passive (Commanditary) partners. Keywords: Commercial Law Law (KUHD), Law no. 40 of 2007 concerning Limited Liability Companies, Permenkumham No. 17 of 2018.